The Onna-bugeisha: Redefining the Female Warrior - Rodríguez Gómez, Mariana (México y la Cuenca del Pacífico, 2026)
This work explores the historical impact of the Onna-bugeishas, Japanese female warriors who defied gender norms and patriarchal structures. Traditionally seen as isolated figures, the objective of this study is to reposition them as essential contributors to gender equality. By analyzing iconic figures like Empress Jing?, Tomoe Gozen, and H?j? Masako, it traces their challenge to Confucian ideology and male-dominated social hierarchies. The theoretical framework integrates feminist historiography to assess the socio-political influence of these warriors. Methodologically, exploratory historical study validates their roles. Findings reveal a consistent resistance pattern among the Onna-bugeishas, establishing a symbolic and practical foundation for future gender equality movements. Their legacy is a testament to women’s influence within historical Japanese society.